2005
DOI: 10.1182/blood-2004-08-3269
|View full text |Cite
|
Sign up to set email alerts
|

SAP controls the cytolytic activity of CD8+ T cells against EBV-infected cells

Abstract: IntroductionX-linked lymphoproliferative (XLP) disease is a severe immunodeficiency characterized by variable clinical phenotypes, including fatal infectious mononucleosis, malignant B-cell lymphoma, and progressive dysgammaglobulinemia. 1 The gene responsible for XLP (SH2D1A) encodes for SAP (SLAM [signaling lymphocyteactivation molecule]-associated protein), or SH2D1A, a natural killer (NK) and T-cell-specific signaling adaptor protein. [2][3][4] Mutations in the SH2D1A gene have been detected in patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
137
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(148 citation statements)
references
References 39 publications
7
137
0
Order By: Relevance
“…24,27,28 However, our findings suggest that the loss of SAP also undermines the priming of naive CD8 C T cells by B cell APCs and thus, limits the repertoire of T cells specific for infected B cells generated upon EBV infection. In addition, an elegant study showed that SAP is important for the generation or homeostasis of EBV-specific memory CD8…”
Section: Sap-deficiency Compromises Immunity Toward Ebv By Diminishinmentioning
confidence: 40%
See 1 more Smart Citation
“…24,27,28 However, our findings suggest that the loss of SAP also undermines the priming of naive CD8 C T cells by B cell APCs and thus, limits the repertoire of T cells specific for infected B cells generated upon EBV infection. In addition, an elegant study showed that SAP is important for the generation or homeostasis of EBV-specific memory CD8…”
Section: Sap-deficiency Compromises Immunity Toward Ebv By Diminishinmentioning
confidence: 40%
“…[24][25][26][27][28] Although multiple immune defects have been attributed to SAP deficiency, [5][6][7] it remains unclear how SAP facilitates control of EBV infection and whether dysfunction of one or more immune cell types underlies the vulnerability of XLP patients to EBV and B cell malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, defects in SAP are associated with inherited X-linked lymphoproliferative syndrome, which is characterized by a dysregulated immune response to infection by Epstein-Barr virus, B cell lymphomas, and dysgammaglobulinemia (4). Notably, blockade of 2B4 in wildtype cytotoxic T lymphocytes results in defects analogous to those observed in SAP-deficient cytotoxic T lymphocytes (6). Furthermore, CD150-, NTB-A-, and Ly-9-deficient mice also show similar T cell defects (7)(8)(9).…”
mentioning
confidence: 99%
“…Conflicting data exist on the regulation of SAP in human T cells. While two reports describe an upregulation of SAP [20,21], one report finds a downregulation of SAP after T cell activation [22]. IL-2 stimulation of mouse NK cells was reported to result in an increased SAP expression [17].…”
mentioning
confidence: 99%